Perceived Parenting Styles as a Moderator Between Childhood Fantasy Play and Creativity in Early Adulthood - Talitha Maurilla; Naomi Soetikno; Fransisca Iriani Roesmala Dewi (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2026)
Creativity is a crucial skill for adapting to the demands of the modern world, and early experiences may play a vital role in its development. This study investigated the relationship between childhood fantasy play and creativity in early adulthood, as well as the moderating role of perceived parenting styles. A non-experimental quantitative design was employed using purposive sampling. Participants were 387 individuals aged 18 to 25 who had lived with their parents between the ages of 2 and 7. Data were collected through an online questionnaire and analyzed using Jeffrey’s Amazing Statistics Program (JASP). Results revealed a significant positive correlation between childhood fantasy play and adult creativity (r = 0.413, p < 0.001). However, perceived parenting styles, both paternal and maternal, did not significantly moderate this relationship. These findings indicate that engaging in imaginative play during childhood contributes meaningfully to creativity in adulthood, and this influence remains consistent regardless of how parenting is later recalled. The study adds to the understanding of how early life experiences shape long-term personal development.